1995
DOI: 10.1055/s-2007-973010
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Speed Skaters to Treadmill Low Walking and Cycle Ergometry

Abstract: Speed skaters have previously relied on cycle ergometry for physiological testing. Current evidence suggests skate-specific testing might be more appropriate. Unlike cycling, skating and off-ice low walk training involves a 'crouched' posture, placing the quadriceps in static contraction. This may compromise blood flow to working muscles and influence VO2. We compared physiological variables between skate-specific treadmill low walking (LW) and cycle ergometry (BK). Skaters (N = 8) performed LW and BK to fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…De Boer et al 28 found greater RER and V ̇E maximal values during inline compared to on ice maximal skating tests, with no significant differences in V ̇O2max, and a more upright posture during inline skating. Differences in RER could be related to decreased V ̇E, as suggested by Rundell and Pripstein 12 , or could be linked to a decreased [La]peak possibly caused by a more pronounced blood flow occlusion and the associated decrease in lactate efflux 29 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…De Boer et al 28 found greater RER and V ̇E maximal values during inline compared to on ice maximal skating tests, with no significant differences in V ̇O2max, and a more upright posture during inline skating. Differences in RER could be related to decreased V ̇E, as suggested by Rundell and Pripstein 12 , or could be linked to a decreased [La]peak possibly caused by a more pronounced blood flow occlusion and the associated decrease in lactate efflux 29 .…”
Section: Discussionmentioning
confidence: 92%
“…Despite the similarities found between treadmill and slide board skating, V ̇Emax, RERmax and [La]peak were significantly smaller during the slide board test and ES were moderate to large, pointing out for meaningful differences (Table 1). These findings were unexpected and might be related to slight differences in body posture adopted on the slide board, since at smaller knee and/or hip angles the ventilatory response can be altered because of mechanical limitations during skating 12,28 . De Boer et al 28 found greater RER and V ̇E maximal values during inline compared to on ice maximal skating tests, with no significant differences in V ̇O2max, and a more upright posture during inline skating.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Skaters typically reach a lower _ V O 2 during maximal speed skating compared to a maximal eort in cycling or running (Ingen Schenau et al 1983;Kandou et al 1987;Rundell and Pripstein 1995). It was suggested that this dierence could be attributed to the absence of a powerful plantar¯exion, and hence a reduction of eective muscle mass, with conventional skates (Ingen Schenau et al 1996).…”
Section: Discussionmentioning
confidence: 99%